Reply to: Heart Failure With Preserved Ejection Fraction in Older Adults. Issue 3 (20th December 2019) - Matsushita, Kenichi; Harada, Kazumasa; Miyazaki, Tetsuro; Miyamoto, Takamichi; Kohsaka, Shun; Iida, Kiyoshi; Yamamoto, Yoshiya; Nagatomo, Yuji; Yoshino, Hideaki; Yamamoto, Takeshi; Nagao, Ken; Takayama, Morimasa
Abstract : This letter comments on the letter by Asit Shil .